Anterior cruciate ligament reconstructed individuals demonstrate slower reactions during a dynamic postural task. (21st May 2020) - Armitano‐Lago, Cortney N.; Morrison, Steven; Hoch, Johanna M.; Bennett, Hunter J.; Russell, Daniel M.
Abstract : Introduction: To determine whether individuals with a history of anterior cruciate ligament reconstruction (ACLR) exhibit altered neuromotor function compared to healthy controls. It was hypothesized that the ACLR group would have slower postural responses compared to healthy individuals of similar age. Materials and Methods: Sixteen adults with a unilateral ACLR and 16 matched healthy controls participated. General assessments of neuromotor function were gathered and included measures of reaction time (both seated and postural conditions), walking ability, balance, ankle ROM, proprioception, knee joint laxity, patellar tendon reflex latency, and quadriceps strength. Data were analyzed using mixed generalized linear models with between‐subject (ie, controls, ACLR) and within‐subject factors (ie, affected, unaffected limb). Results: Individuals with an ACLR exhibited a significant slowing of their postural reaction times compared to the control individuals. The ACLR group was slower under both the simple (ACLR: 484 ± 6.17 ms, control: 399 ± 1.95 ms) and choice reaction time conditions (ACLR: 550 ± 43 ms, control: 445 ± 43 ms). No other group differences were found in any of the other measures. Conclusion: Overall, ACLR individuals had a reduced ability to respond quickly under more challenging postural conditions (ie, stepping response). This finding would indicate that the impact of an ACLR is not purely mechanical and restricted to the joint. Rather, injury and reconstruction of the ACL impact neural mechanisms, altering individuals' ability to respond under challenging balance tasks.